Investigation of in-field devices for underwater surveying of reef structures - Mufti, Alaa; Parnum, Iain; Belton, David; Helmholz, Petra (2019)
This poster presents the results of the first data collection with a multibeam echo-sounder system over two pre-fabricated Artificial Reefs structures and the surrounding seafloor located 11 km south of the west end of Rottnest Island, Western Australia. As the structure and dimensions are well understood through engineering diagrams, they were compared with the multibeam point cloud. Using the reef structures, the dynamic offsets of the multibeam system were further improved by the addition of –0.957° in the pitch alignment. The RMS between the multibeam measurements and the engineering diagram was 1.167 m.